ANALISIS LEARNING OBSTACLE KEMAMPUAN NUMERASI SISWA SD PADA PEMBELAJARAN TATAP MUKA DIDASARKAN PADA ASPEK SOCIOMATHEMATIC NORM - Syahnia Nur Jamalia; Samsul Maarif (Jurnal Tematik, 2023)
This study aims to describe the learning barriers to students' numeracy skills based on aspects of socio-mathematical norms. This type of research is a case study with a qualitative approach. The subjects of this research are fourth-grade students of SDS Islam Assa'adah, East Jakarta, for the academic year 2021“2022. Data collection techniques used in this research include tests and interview techniques. The results showed that students' numeracy skills were more dominant at the moderate level with a percentage of 50% and socio-mathematical norms were also more dominant at the medium level category with a percentage of 64%. The test results were then validated by interviewing a group of six students with varying levels of ability.